English as a Foreign Language (EFL) Students’ Perception of Critical Literacy in Indonesian Context: Persepsi Mahasiswa Bahasa Inggris sebagai Bahasa Asing (EFL) tentang Literasi Kritis dalam Konteks Indonesia - Emmas Mas Pupah; Nisa Syuhda (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2024)
This research explored the English as a Foreign Language (EFL) students’ perspectives about critical literacy and the possibility of implementing critical literacy practices in an Indonesian context by revealing the opportunities and challenges. Ten English education students who have taken a critical literacy course at one of the state universities in Yogyakarta, Indonesia, were involved in this study. Their views related to critical literacy, the benefits, and the opportunities for practicing it were gathered through unstructured interview methods. The data were analyzed using inductive content analysis. The results of the data analysis revealed that all the participants realized the importance of critical literacy in Indonesia toward the enhancement of critical awareness and social justice. The finding also holds firm conviction in its suitability for implementation since the critical literacy is a mandate in Pancasila Principle. The students also revealed the little teachers’ understanding of critical literacy as the obstacle to implementing critical literacy in Indonesia. Abstrak Penelitian ini mengeksplorasi perspektif mahasiswa EFL (Bahasa Inggris sebagai Bahasa Asing) tentang literasi kritis dan kemungkinan penerapan praktik literasi kritis dalam konteks Indonesia dengan mengungkap peluang dan tantangannya. Penelitian ini melibatkan sepuluh mahasiswa Prodi Pendidikan Bahasa Inggris yang telah mengambil Mata Kuliah Literasi Kritis di salah satu universitas negeri di Yogyakarta, Indonesia. Pengumpulan data didapatkan melalui wawancara tidak terstruktur tentang pandangan mereka terhadap literasi kritis, manfaat, dan peluang dalam mempraktikkannya. Data dianalisis dengan menggunakan analisis isi induktif. Hasil analisis data menunjukkan bahwa semua partisipan menyadari pentingnya literasi kritis di Indonesia untuk meningkatkan kesadaran kritis dan keadilan sosial. Temuan ini juga menegaskan betapa pentingnya mengimplementasikan literasi kritis, yang merupakan pengamalan dari sila-sila Pancasila. Para mahasiswa juga mengungkapkan bahwa kurangnya pemahaman guru terhadap literasi kritis menjadi kendala dalam penerapan literasi kritis di Indonesia.